Pengaruh Struktur Modal, Investment Opportunity Set Dan Kepemilikan Institusional Terhadap Nilai Perusahaan: Studi Empiris Pada Perusahaan Sub Sektor Food & Beverage yang Terdaftar di BEI Periode 2019 - 2023 - Arenti Tessa Berliana; Martini Martini (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The study aims to determine and analyze the effect of Capital Structure, Investment Opportunity Set adn Insstitutional Ownership on company value of Food & Beverage Sub Setor companies listed on the Indonesian Stock Exchange (IDX) from 2019 – 2023. This study usnig a puposive sampling technique and obtained 39 companies. Data analysis was conducted through multiple linear regression with SPSS version 22 and Microsoft Excel 2019. The findings reveal that Capital Structure, Investment Opportunity Set and Institutional Ownership each have a poitive and significant effect on company value.